Health of children born to women after radiation and chemotherapy for Hodgkin's lymphoma - A. A. Danilenko; S. V. Shakhtarina; L. N. Shchelkonogova; V. V. Pavlov (Онкогематология, 2014)
Presents data of the health of 411 children (I generation) and 23 children (II generation) born to 340 women received chemotherapy or radiotherapy due to Hodgkin’s lymphoma. Most children were born healthy. Congenital pathology were registered in 19 (14.6 %) children of I generation and 1 (4.3 %) – of II generation. In 3 children of I generation Hodgkin,s lymphoma was diagnosed.